Pengaruh Budaya Organisasi Dan Kepemimpinan Kepala Sekolah Terhadap Kompetensi Dan Kinerja Guru Pada Yayasan Perguruan Sultan Agung Pematangsiantar - Kevin Indajang; Jufrizen Jufrizen; Azuar Juliandi (Universitas Negeri Medan, 2020)
The purpose of this research was to test and analyze the influence organizational culture and principals’s leadership on teacher’s performance which is moderated by teacher’s competence. The sample in this reseacrh was 98 permanent teachers from the Yayasan Perguruan Sultan Agung Pematangsiantar. Data collection was carried out by means of the questionnaire method. Methods used in this research were structural equation model partial least square (SEM-PLS). The results of this study indicate organizational culture does not significantly influence the teacher’s performance, the principal's leadership significantly influences the teacher’s performance, teacher competency significantly influences the teacher’s performance. Teacher’s competence does not moderate the relationship between organizational culture and teacher, teacher competence does not moderate the relationship between the principal's leadership and the teacher's performance of Yayasan Perguruan Sultan Agung Pematangsiantar.